Mode-locked Tm-doped fiber laser based on iron-doped carbon nitride nanosheets. (30th October 2017) - Luo, Yongfeng; Zhou, Yan; Tang, Yulong; Xu, Jianqiu; Hu, Chenxia; Gao, Linfeng; Zhang, Haoli; Wang, Qiang
Abstract: Solution based nanosheets of iron-doped graphitic carbon nitrides (Fe-g-CN) have been prepared and their optical properties (both linear and nonlinear) are studied. These two-dimensional (2D) nanosheets show an absorption spectrum extending to over 2 µ m, and in particular they possess strong nonlinear (saturable) absorption in the 2 µ m spectral region. A saturable absorber (SA) manufactured from 2D Fe-g-CN nanosheets gives a modulation depth and saturation intensity of 12.9% and 8.9 MW cm −2, respectively. This SA is further used to mode-lock thulium-doped fiber lasers, producing 2 µ m laser pulses with a duration of 16.6 ps (dechirped to 2.2 ps), an average power of 96.4 mW, a pulse energy of 6.3 nJ, and a repetition rate of 15.3 MHz. As a new type of 2D nonlinear material with strong modulation capabilities, solution-based Fe-g-CN nanosheets can be potentially integrated into photonic and optoelectrionic devices, particuarly in the 2 µ m spectral region.